Recent Advances in Long-Acting Drug Delivery and Formulations - Abdelkader, Hamdy; Al-Fatease, Adel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue titled "Recent Advances in Long-Acting Drug Delivery and Formulations" encompasses versatile and innovative research domains of oral, ocular, brain, and topical delivery systems and chemical approaches (e.g., prodrugs), highlighting the progress made in identifying excipients (e.g., basic amino acids to ameliorate gastric side effects of non-steroidal anti-inflammatory drugs (NSAIDs)), polymers, and molecular targets to achieve more effective sustained release systems and safer medicine. In this Special Issue, 78 authors have contributed, with eleven original research articles spanning five continents (Asia, Europe, Africa, North America, and Australasia) providing important insights into the pharmaceutical sciences.